Liquid temperature effect on the hydraulic shock wave velocity in polyethylene pipes - I. R. Antypas; A. G. Dyachenkо; Saed Bakir Imad (Advanced Engineering Research, 2022)
Introduction. Providing people with high quality drinking water has always come first. However, its transportation through pipeline systems was often associated with some problems, such as the temperature of the water and the environment, as well as the possibility of water hammer on certain pipe sections. This was especially true for systems that use polyethylene pipes. Temperature is a key factor affecting the flexibility properties of polyethylene pipes, and it affects not only the design, but also the investment in the development of water supply networks. The purpose of these studies was to study the effect of water and ambient temperature on the density, properties of the pipe material and the speed of propagation of a hydraulic shock wave in polyethylene pipes.Materials and Methods. In the experiments performed, the method of field research was used, when tests are carried out on specialized equipment on samples specially made for the pursued purposes. Here, samples of high-density polyethylene pipes were used, which were subjected to tensile tests on a tensile testing machine, and each experiment was carried out three times.In the course of the experiments, the samples were exposed to certain temperature regimes (both external and internal), while the influence of the hydrodynamic pressure of the liquid in the pipe was also investigated, as a result of the change in time of the liquid velocity in its sections. To do this, the samples were supplied with liquid under a certain pressure in order to find out the influence on the pipes of an effect known as water hammer.Results. In the course of the research, it was found that the value of the elastic modulus of high-density polyethylene PE100 decreases with increasing water temperature, and the decrease at a temperature of 60° C reaches 60.21% compared to its value at a water temperature of +4° C. Based on the results of experiments to determine the effect of the elastic modulus of polyethylene with increasing temperature, an exponential equation was derived to calculate the value of the polyethylene coefficient as a function of time E = 1.312e-0,01t with the correlation coefficient R2 = 0.988 ; and based on the results of the studies carried out to calculate the value of the propagation velocity of a hydraulic shock wave, an exponential equation was derived as a function of time C = 275.9e-0,01t with the coefficient correlation R2 = 0.987 .Discussion and Conclusions. In the course of the research, it was found that such a phenomenon as water hammer has a harmful effect on the pipe walls, which, if possible, should be avoided even at the design stage of the water supply network. During the experiments, it was found that with an increase in temperature, the values of the elastic modulus of polyethylene decreased with a simultaneous decrease in the values of the propagation velocity of the hydraulic shock wave.